Loan market equilibrium with difference of opinion and imperfect competition - Ari Hyytinen (The Research Institute of the Finnish Economy (ETLA), 2002)
Difference of opinion between banks and borrowers influences the competitiveness of loan markets: the more optimistic the borrowers, the more elastic the demand for loans. This reduces lending rates, decreases the expected profits of banks and discourages entry by banks. – banking ; competition ; optimism ; difference in opinion ; entry
Keywords: D43; G21; 330; Bankgeschäft; Wettbewerb; Verhaltensökonomik; Marktstruktur; Theorie